2004
DOI: 10.1111/j.1460-2466.2004.tb02637.x
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Inoculation in Televised Political Debates

Abstract: This study was the first to examine the potential of inoculation in televised political debates. The experiment confirmed the efficacy of inoculation in conferring resistance to the influence of counterattitudinal attack messages launched during debates. Inoculated participants with a preference toward a candidate were more resistant than the control group to the opposing candidate's counterattitudinal attacks. The study also explored the potential of inoculation to strengthen receivers' normative attitudes, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Some hedonistic-based communication theories identified by Pavitt (2010) include Bandura's (1986) social learning theory, Witte's (1992) extended parallel processing model, Nabi's (1999) cognitive-functional model for the influence of negative affective reactions, McGuire's (1964) inoculation theory, and Giles's communication accommodation theory (see Giles & Ogay, 2007). Political communication has delved into the use of some of these theories (e.g., Pfau's use of inoculation theory; see An & Pfau, 2004;Pfau, Kenski, Nitz, & Sorenson, 1990), and there has been some work on the study of discrete emotional reactions to political messages that parallels the work of Nabi (e.g., Holbert & Hansen, 2006;Hullett, Louden, & Mitra, 2003). However, a vast majority of hedonistic-based theories have not seen the light of day in the field, and none of them have been explored to the extent enjoyed by understanding-or consistency-based approaches.…”
Section: Shifting Dominant Preferences Explanatory Principles and Tmentioning
confidence: 99%
“…Some hedonistic-based communication theories identified by Pavitt (2010) include Bandura's (1986) social learning theory, Witte's (1992) extended parallel processing model, Nabi's (1999) cognitive-functional model for the influence of negative affective reactions, McGuire's (1964) inoculation theory, and Giles's communication accommodation theory (see Giles & Ogay, 2007). Political communication has delved into the use of some of these theories (e.g., Pfau's use of inoculation theory; see An & Pfau, 2004;Pfau, Kenski, Nitz, & Sorenson, 1990), and there has been some work on the study of discrete emotional reactions to political messages that parallels the work of Nabi (e.g., Holbert & Hansen, 2006;Hullett, Louden, & Mitra, 2003). However, a vast majority of hedonistic-based theories have not seen the light of day in the field, and none of them have been explored to the extent enjoyed by understanding-or consistency-based approaches.…”
Section: Shifting Dominant Preferences Explanatory Principles and Tmentioning
confidence: 99%
“…This is believed to increase resistance to the challenging information, much in the same way that a vaccine confers resistance to a virus by exposing the body to a weakened version of that virus. A large body of research has applied and tested inoculation interventions in contexts including health, politics and education (An & Pfau 2004;Banas & Rains 2010;Compton et al 2016). These findings are important, because there is some evidence that the perception of a scientific consensus can serve as a "gateway" belief that increases belief in the reality of climate change, and increases support for public action (van der Linden et al 2015(van der Linden et al , 2019; but c.f.…”
Section: Introduction To Empirical Studymentioning
confidence: 99%
“…Televised debates are a public communication staple in contemporary United States political campaigns and an integral part of the campaign landscape. In both national and state political campaigns, televised debates attract larger and more diverse audiences than any other communication form (An & Pfau, 2004). No other event is so interwoven within the foundational principles of a democracy as an open debate in which candidates have the opportunity to speak directly to voters and voters have the opportunity to listen and compare their arguments.…”
Section: Troductiomentioning
confidence: 99%
“…Although a number of studies since the "Great Debates" of 1960 have reported that the primary impact of televised debates is the reinforcement of viewers' political predispositions, the bulk of empirical studies have found that debates manipulate viewers' attitudes toward political candidates. Televised debates can influence voters' candidate evaluations, including perceptions of candidates as caring and charismatic individuals (An & Pfau, 2004).…”
Section: A Eed For Additional Researchmentioning
confidence: 99%
See 1 more Smart Citation